Organizational reputation risk management as a component of the dynamic capabilities management process1 - Krzakiewicz Kazimierz; Cyfert Szymon (Management, 2015)
Intangible assets, such as reputation, brand value, strategic position, alliances, knowledge, human capital, play an increasingly important role in shaping the market value of an organization. At the same time, in the literature it is emphasized that the attribute of intangibility translates into an increased risk of destruction or impairment of assets. Thus, the research problem associated with the analysis of organizational reputation risk management as a component of the dynamic capabilities management process should be considered important from the point of view of management science. The study attempts to outline the concept of dynamic capabilities, define the concept of risk and subsequently discuss the relationship between dynamic capabilities and organizational reputation risk management.